Relevance of targeting RET/PTC junction oncogene and Wnt/β-catenin pathway in the treatment of papillary thyroid carcinoma: skill of 8-year work - Massaad-Massade, L. (Вiopolymers and Cell, 2014)
Papillary thyroid carcinoma (PTC) is the most common endocrine gland malignancy and occurs frequently due to the radiation exposure. PTC is characterized by the paracentric inversion in chromosome 10 leading to the fusion of RET with several genes present in thyroid named PTC. The RET/PTCs junction oncogenes are present in around 80 % of papillary thyroid carcinoma, the most frequent ones are RET/PTC1 and RET/PTC3. Interestingly, RET/PTCs are found only in the tumour cells and not in the surrounding normal tissues, therefore, they represent a good target for RNA interference strategies. We aimed, on the one hand, to inhibit dedifferentiation due to the RET/PTC junction oncogene by siRNA and, on the other hand, to investigate a role of Wnt/β-catenin pathway in the regulation of a tissue-specific transcription factor, the thyroid transcription factor-1 (TTF-1) essential for the differentiation of the thyroid. In this paper we summarised our main results obtained during eight years that pointed a new therapeutic strategy for papillary thyroid carcinoma.